2018
DOI: 10.1007/s00520-018-4191-4
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth applied to physical activity during cancer treatment: a feasibility, acceptability, and randomized pilot study

Abstract: Surprisingly, the level of exercise in group R did not significantly increase, but self-reported fatigue and quality of life were improved. This study underlines that inexpensive sharing of time, human, and financial means, through a protocol of physical activity, improves patient health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 17 publications
1
48
0
2
Order By: Relevance
“…A total of 24 studies were included in this review; 11 studies were delivered via synchronous and asynchronous methods, respectively, with 2 studies using a combined approach ( Figure 1 ). The studies were predominantly delivered in the United States with 13 studies [ 37 , 41 - 52 ]; 3 in Australia [ 35 , 36 , 53 ], South Korea [ 33 , 54 , 55 ], and the Netherlands [ 56 - 58 ]; and 1 in Canada [ 59 ] and France [ 60 ]. The total sample size was 4583, ranging from n=18 to n=641.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 24 studies were included in this review; 11 studies were delivered via synchronous and asynchronous methods, respectively, with 2 studies using a combined approach ( Figure 1 ). The studies were predominantly delivered in the United States with 13 studies [ 37 , 41 - 52 ]; 3 in Australia [ 35 , 36 , 53 ], South Korea [ 33 , 54 , 55 ], and the Netherlands [ 56 - 58 ]; and 1 in Canada [ 59 ] and France [ 60 ]. The total sample size was 4583, ranging from n=18 to n=641.…”
Section: Resultsmentioning
confidence: 99%
“…There were a range of different cancer types targeted during the study interventions: 7 unspecified cancer types [ 45 , 49 , 50 , 52 , 55 - 57 , 60 ]; 6 breast cancer [ 33 , 35 , 42 , 51 , 54 , 61 ]; 2 colon or colorectal [ 36 , 43 ]; 2 breast, prostate, or colorectal [ 44 , 59 ]; 2 melanoma [ 41 , 53 ]; and 1 each of breast/colon or rectal [ 37 ], colorectal or prostate [ 58 ], prostate [ 46 ], and urothelial cell carcinoma [ 47 ]. The majority of studies focused on posttreatment (also reported as survivors) with 17 studies [ 33 , 36 , 37 , 41 , 43 - 45 , 49 - 56 , 59 , 61 ], 6 studies included patients during active cancer treatment (2 used survivors and active cancer treatment) [ 35 , 42 , 47 , 57 , 58 , 60 ], and 1 study included patients undergoing surveillance for their cancer [ 46 ]. Of the 24 studies included in this review, 19 provided data on a measure of physical activity behavior change [ 33 , 35 - 37 , 42 - 45 , 48 - 50 , 54 - 57 , 59 ] and 9 studies provided data on a measure of dietary behavior change [ 33 , 36 , 42 , 44 - 47 , 54 , 56 ]; 2...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations